Implementasi Teknologi Kecerdasan Buatan dalam Operasional Lembaga Keuangan Syariah - Azza Naufi Tiam Martha Putri; Nurhisam, Luqman (Universitas Muhammadiyah Jember, 2025)
This study examines how the application of Artificial Intelligence (AI) Technology aims to improve the operations of Islamic Financial Institutions along with the development of financial product innovation in technological advances in the era of disruption. In addition, the need for fast and accurate services and increasingly tight competition in the financial industry. The focus of this study is to analyze how Artificial Intelligence (AI) Technology can support the operations of Islamic Financial Institutions in improving operational efficiency and financial risk management. The research method uses normative juridical research, which is a legal research method by examining relevant literature or secondary materials in the research. The results of the study show that the use of Artificial Intelligence (AI) Technology can accelerate the operational process of Islamic Financial Institutions in financial transactions, improve the quality of financial services and reduce the risk of loss (risk management) through better data management and analysis. In its operations, Islamic Financial Institutions are required to comply with the rules set by the Financial Services Authority (OJK) and the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) to be in line with sharia principles (Sharia Compliance).